Multi-Centre Study on Cardiovascular Risk Management on Patients Undergoing AAA Surveillance. (July 2017) - Saratzis, A.; Dattani, N.; Brown, A.; Shalhoub, J.; Bosanquet, D.; Sidloff, D.; Stather, P.; ,
Abstract : Background: The risk of cardiovascular events and death in patients with abdominal aortic aneurysms (AAA) is high. Screening has been introduced to reduce AAA related mortality; however, after AAA diagnosis, cardiovascular modification may be as important to patient outcomes as surveillance. The aim of this study was to assess cardiovascular risk reduction in patients with small AAA. Methods: Institutional approval was granted for The Vascular and Endovascular Research Network (VERN) to retrospectively collect data pertaining to cardiovascular risk reduction from four tertiary vascular units in England. Patients with small AAA (January 2013–December 2015) were included. Demographic details, postcode, current medications, and smoking status were recorded using a bespoke electronic database and analysed. In a secondary analysis VERN contacted all AAA screening units in England and Wales to assess their current protocols relating to CV protection. Results: In total, 1053 patients were included (mean age 74 ± 9 years, all men). Of these, 745 patients (70.8%) had been prescribed an antiplatelet agent and 787 (74.7%) a statin. Overall, only 666 patients (63.2%) were prescribed both a statin and antiplatelet. Two hundred and sixty eight patients (32.1%) were current smokers and the proportion of patients who continued to smoke decreased with age. Overall, only 401 patients (48.1%) were prescribed a statin, antiplatelet, and had stopped smoking. In the secondary analysis 38 AAA screening units (84% national coverage) replied. Thirty-one units (82%) suggest changes to the patient's prescription; however, none monitor compliance with these recommendations or assess whether the general practitioner has been made aware of the AAA diagnosis or prescription advice. Conclusion: Many patients with small AAA are not prescribed an antiplatelet/statin, and still smoke cigarettes, and therefore remain at high risk of cardiovascular morbidity and mortality. National guidance to ensure this high risk group of patients is adequately protected from poor cardiovascular outcomes is lacking.